2021
DOI: 10.21203/rs.3.rs-1183528/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Viral Haemorrhagic Fevers and Malaria Co-Infections Among Febrile Patients Seeking Health Care in Tanzania

Abstract: Background: In recent years there have been reports of viral haemorrhagic fever (VHF) epidemics in Sub-Saharan Africa where malaria is endemic. VHF and malaria have overlapping clinical presentations making differential diagnosis a challenge. The objective of this study was to determine the prevalence of selected zoonotic VHFs and malaria co-infections among febrile patients seeking health care in Tanzania. Methods: This facility-based cross-section study was carried out in Buhigwe, Kalambo, Kyela, Kilindi, Ki… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 18 publications
0
2
0
Order By: Relevance
“…The virus is named after the city of Marburg, Germany, where the first cases were identified [11] . The virus is closely related to the Ebola virus, and both viruses belong to the Filoviridae family [7,8] .…”
Section: History Epidemiology and Clinical Pathology Of Marburg Virus...mentioning
confidence: 99%
See 1 more Smart Citation
“…The virus is named after the city of Marburg, Germany, where the first cases were identified [11] . The virus is closely related to the Ebola virus, and both viruses belong to the Filoviridae family [7,8] .…”
Section: History Epidemiology and Clinical Pathology Of Marburg Virus...mentioning
confidence: 99%
“…However, bordering countries with frequent outbreaks, geographical factors, cultural practices, and low public health awareness makes Tanzania vulnerable with increased susceptibility to VHFs [6,7] . In the absence of these outbreaks, still, several studies showed a seroprevalence of different VHFs, including Crimean-Congo hemorrhagic fever, Ebola virus disease, MVD, Rift Valley fever, and yellow fever in different geographical areas in Tanzania [7][8][9] . This article highlights the epidemiology, clinical pathology of MVD, the situation of the outbreak in Tanzania, and stresses on the interventions, which should be considered in the prevention and control of such outbreaks.…”
Section: Introductionmentioning
confidence: 99%